Eco Fazenda Mundo Novo e sua contribuição como atrativo turístico em Canindé de São Francisco/SE - Santana, Maria Ledivania de (2015)
This study aims to reveal the contribution of Eco Farm New World as a tourist attraction in Caninde de Sao Francisco / SE. Present new possibilities that can boost the development of the town of Caninde de Sao Francisco / SE as an important link between tourism and local development at the same time identify the tourist attractions on site with an emphasis on Eco Farm New World and its relationship with the tourism in the municipality, in order to assess the tourist attractions and the infrastructure of the locality; analyze its importance for tourism in the municipality; relate the tourist activities already consolidated in Caninde de Sao Francisco / SE and explain the strategies used in Eco Farm New World for the implementation of tourist itineraries. Therefore, it is important to note the recognition of products / attractions and the quality of services offered, growth, consolidation, maturity and decline of products along with the importance that it has for the local community and visitors. The first step will be through literature, proceeded in reading sources such as books, articles, monographs in libraries and internet, facilitating analyze diverse concepts on the subject. Soon after this research, field work will take place, with on-site observations. In the first chapter are the main theories on the subject. The second chapter will describe the city in its historical formation, evolution, emergence and characterization of tourism in the region of Caninde de Sao Francisco / SE. The third and final chapter, will show the Eco Farm New World as a tourist attraction in Canyon script.